1999
DOI: 10.1046/j.1360-0443.1999.94226910.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Fagerstrom test for nicotine dependence and of the Heaviness of Smoking Index among relatively light smokers

Abstract: In a population of relatively light smokers, FTND and HSI seem to measure little more than the number of cigarettes per day. Designing a new and more broadly applicable test of addiction to cigarettes is a research priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
181
5
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 299 publications
(208 citation statements)
references
References 24 publications
(32 reference statements)
13
181
5
9
Order By: Relevance
“…The findings of this study diverged from other studies (Etter & Perneger, 1999;Uysal et al, 2004) in terms of the high percentages (88% and 91% respectively) of smokers who reported their first daily cigarette within 30 minutes of waking and this cigarette as the least desirable to give up, supporting the pressing need to restore systemic nicotine levels. The SDS-khat established the psychological khat dependence, so there remains a knowledge gap with respect to the physical dependence on khat related stimulants such as cathinone measured by time of first intake after waking.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The findings of this study diverged from other studies (Etter & Perneger, 1999;Uysal et al, 2004) in terms of the high percentages (88% and 91% respectively) of smokers who reported their first daily cigarette within 30 minutes of waking and this cigarette as the least desirable to give up, supporting the pressing need to restore systemic nicotine levels. The SDS-khat established the psychological khat dependence, so there remains a knowledge gap with respect to the physical dependence on khat related stimulants such as cathinone measured by time of first intake after waking.…”
Section: Discussioncontrasting
confidence: 99%
“…The key findings of the study were as follows: two factors were found to fit the data and the internal reliability of the scale was low alongside its underlying subscales. The study lends further support to the bi-dimensionality of the scale as reported in other cultural settings (Payne et al, 1994;Etter & Perneger, 1999;Haddock et al, 1999;Radzius et al, 2003). This study confirmed as well that Factor 1 reflects the degree of urgency to restore nicotine levels to a given threshold after waking whilst Factor 2 reflects the persistence with which nicotine concentration are maintained during waking hours (Radzius et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…4,5 These metrics are readily and conveniently employed; however, the psychometric properties of these measures are tenuous, with some studies demonstrating poor to moderate internal consistency for the measures [6][7][8] and others indicating that the FTND is unstable when subjected to factor analysis. [9][10][11] While the FTND and HSI measures provide a metric for the magnitude of nicotine seeking behavior, they appear unsuited to determine why or what factors contribute to dependence, motivate continued use, and drive relapse after a quit attempt. To better capture the multifaceted nature of nicotine dependence, Piper and colleagues 1 developed the 68-item Wisconsin Inventory of Smoking Dependence Motives (WISDM).…”
Section: Psychometric Characteristics Of the Brief Wisconsin Inventormentioning
confidence: 99%